ANALYSIS OF INVENTORY MANAGEMENT AND ITS IMPACT ON OPERATIONAL EFFICIENCY: a case study in a company specializing in electrical and hydraulic materials - Aguiar, Guilherme; Terazzi, Luis Fernando (Revista Interface Tecnológica, 2024)
This article explores the importance of inventory management for operational efficiency in a company specializing in electrical and hydraulic materials. The objective is to assess how inventory management can optimize operational performance. The research was conducted through a case study involving a detailed analysis of data on inventory management practices, including inventory levels, replenishment times, and demand forecasting accuracy. The results show that implementing advanced inventory control techniques and accurate forecasting significantly improves operational efficiency. A reduction in operational costs and an improvement in market responsiveness were observed. The conclusion reinforces that effective inventory management is crucial for enhancing operational efficiency and gaining a competitive advantage. It is suggested that other companies in the sector consider adopting similar strategies to achieve comparable benefits.